Advanced Devices for Tumor Diagnosis and Therapy. Issue 28 (10th June 2021) - Wang, Lude; Dai, Chendong; Jiang, Lianfu; Tong, Gangling; Xiong, Yunhai; Khan, Karim; Tang, Zhongmin; Chen, Xiang; Zeng, Haibo
Abstract: At present, tumor diagnosis is performed using common procedures, which are slow, costly, and still presenting difficulties in diagnosing tumors at their early stage. Tumor therapeutic methods also mainly rely on large‐scale equipment or non‐intelligent treatment approaches. Thus, an early and accurate tumor diagnosis and personalized treatment may represent the best treatment option for a successful result, and the efforts in finding them are still in progress and mainly focusing on non‐destructive, integrated, and multiple technologies. These objectives can be achieved with the development of advanced devices and smart technology that represent the topic of the current investigations. Therefore, this review summarizes the progress in tumor diagnosis and therapy and briefly explains the advantages and disadvantages of the described microdevices, finally proposing advanced micro smart devices as the future development trend for tumor diagnosis and therapy. Abstract : Tumor diagnosis is performed using common procedures, which are slow, costly, and still presenting difficulties in diagnosing tumors at their early stage. Tumor therapeutic methods also mainly rely on large‐scale equipment or non‐intelligent treatment approaches. Advanced smart micro devices are expected to break through the above difficulties and provide new opportunities for tumor diagnosis and therapy.